Plásticos comerciais tratados a plasma para dispositivos ópticos e embalagens alimentícias - Sant'Ana, Péricles Lopes [UNESP] (Universidade Estadual Paulista (Unesp), 2014)
Polyvinychroride (PVC), Polyethylene Teraphthalate (PET) and Polyethylene (PE) are the polymers mos frequently applied in food packaging and, are also amoung the most recycled plastics in the world. Many investigations are necessary to identify alternatives that provide uses for the recycled plastic technology to reduce the consumption of virgin material, thus reducing waste and preverving the environment. It is worth noting that some physicochemical modification techniques of the surface of these materials have been used with partial success. An alternative to these, are the plasma treatments for surface modification, which are cheap, rapid and have good reproducibility. The plasma procedures can also be readly scaled-up. Given these possibilities, the purpose of this study was to investigate the effect of three different plasma methodologies: (i) exposure to low energy plasmas, called Plasma Immersion (PI): (ii) plasma immersion ion implantation (PIII); (iii) thin film deposition by magnetron-sputering (MS), on the surface properties of PVC, PET and PE. For the first procedure (PI), the effects of gas employed, sulfur hexafluoride (SF6) or nitrogen (N2), electrical discharge power of the plasma excitation source (radio frequency) and treatment time were studied on the physico-chemical properties of the surface of the PVC, PET and PE. In treatments using PIII, the effects of the magnitude and cycle time of the applied voltage, and the treatment time one the physical-chemical properties of the surface of PET and PE, were investigated. Using Magnetron-Sputtering (MS) technique, thin films of titanium oxide (TiO2) were obtained by varying the proportion of argon and oxygen gases in the vacuum chamber, the electric discharge of power source. the total gas pressure in the chamber and the applied voltage. Suface wetting properties, morphology and transparency to visible light were obtained immediately after the films from the reactor. The...

O policloreto de Vinila (PVC), Polietileno Tereftalato (PET) e o Polietileno (PE) têm sido os polímeros com amior aplicação para fabricação de embalagens de alimentos e também os mais reciclados atualmente, em todo o mundo. Muitas investigações são necessárias para identificar alternativas que propiciam um fim tecnológico ao plástico reclicado, contribuindo para a preservação ambiental. Como alternativa, destacam-se os Tratamentos a plasma para modificação de superfícies, pelo baixo custo, rapidez, flexibilidade e reprodutividade dos experimentos. Também podem ser dimensionados para produção em larga escala. Diante de tais possibilidades, a proposta foi investigar o efeito de três metodologias distintas de plasma: (i) a exposição a plasma de baixa energia, denominada Imersão em Plasma (IP); (ii) a implantação Iônica por Imersão em Plasma (IIIP); (iii) a deposição de filmes finos pela técnica de Magnetron-Sputerring (MS) nas propriedades superficiais do PVC, PET, e do PE. No primeiro procedimento (IP), investigou-se o efeito composição química, potência de descarga elétrica da fonte de excitação do plasma (radiofrequência), pressão dos gases hexafluoreto de enxofre (SF6) ou nitrogênio (n2), e o tempo de tratamento nas propriedades físico-químicas de superfície de PVC, PET e PE. Nos tratamentos pela técnica de IIIP, investigou-se o efeito do tempo de ciclo da fonte de alta tensão, a voltagem da fonte de alta tensão e o tempo de tratamento nas propriedades físico-químicas de superfície do PET e PE, utilizando-se os mesmos gases. Já pela técnica de MS, filmes finos de Óxido e Titânio (TiO2) foram obtidos e analisados variando-se a proporção de gases Argônio e Oxigênio, a potência de descarga elétrica da fonte, a pressão total de gases na câmara e a voltagem aplicada. O grau de molhabilidade das amostras via ângulo de contato, foi medido pelo método da gota séssil. A rugosidade...
Keywords: Polimeros; Plasma (Gases ionizados); Filmes finos; Embalagens - Industria; Revestimentos para comestiveis; Polymers